1998
DOI: 10.1097/00000658-199804000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Halofuginone-an Inhibitor of Collagen Type I Synthesis-Prevents Postoperative Formation of Abdominal Adhesions

Abstract: ObjectiveTo evaluate the effects of halofuginone, a specific inhibitor of collagen type synthesis, on the postoperative formation of abdominal adhesions in rats. Summary Background Data ResultsThe adhesions formed between the intestinal walls were composed of collagen and were populated with cells expressing the collagen al (1) gene. Regardless of the administration procedure, halofuginone significantly reduced the number and severity of the adhesions. Halofuginone prevented the increase in collagen al (1) ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
55
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 26 publications
1
55
0
2
Order By: Relevance
“…As a consequence, the component became exposed, which is contraindicated by the manufacturer. There were no adhesions in the center of the mesh, as described before in the literature 9,12 . The PP mesh developed 100% of the adhesion in the center.…”
Section: Discussionsupporting
confidence: 62%
“…As a consequence, the component became exposed, which is contraindicated by the manufacturer. There were no adhesions in the center of the mesh, as described before in the literature 9,12 . The PP mesh developed 100% of the adhesion in the center.…”
Section: Discussionsupporting
confidence: 62%
“…We showed that the effect of halofuginone on collagen synthesis was transient, and on halofuginone removal, collagen gene expression in vitro 28 and in a cGvHD patient in vivo 35 returned to control levels. The reduction in the collagen ␣1(I) gene expression in rats, 32 rabbits, 27 and in chickens raised on halofuginone-containing diets for 6 weeks from hatching 45 was achieved at concentrations at which no side effects were apparent. Moreover, in all our experiments involving surgery, such as during abdominal or gynecologic adhesion formations 32,33 no abnormal wound healing was observed in the halofuginone-treated animals.…”
Section: Discussionmentioning
confidence: 98%
“…The reduction in the collagen ␣1(I) gene expression in rats, 32 rabbits, 27 and in chickens raised on halofuginone-containing diets for 6 weeks from hatching 45 was achieved at concentrations at which no side effects were apparent. Moreover, in all our experiments involving surgery, such as during abdominal or gynecologic adhesion formations 32,33 no abnormal wound healing was observed in the halofuginone-treated animals. Using the wound-tumor model in which C6 glioma spheroids were implanted in surgical incisions, acceleration in wound repair was observed in the halofuginone-treated animals.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations